IMMUNOLOGICAL INDICATORS AND THEIR ROLE IN THE PATHOGENESIS OF PERIODONTAL LESIONS IN COMBINATION WITH CHRONIC TONSILLITIS - Djuraeva Ferangiz Khakimovna (NEW APPROACHES IN EDUCATION: PEDAGOGY, INNOVATION, AND DEVELOPMENT, 2026)
Abstract: The interrelationship between periodontal diseases and chronic tonsillitis represents a significant clinical and scientific concern due to shared immunopathological mechanisms. This study explores immunological indicators and their contribution to the pathogenesis of periodontal lesions when associated with chronic tonsillitis. Special attention is given to systemic and local immune responses, including cytokine imbalance, immunoglobulin levels, and cellular immunity dysfunction. The findings highlight how chronic infection in the tonsils may exacerbate periodontal tissue destruction through immune dysregulation. Understanding these mechanisms provides a basis for improved diagnostic approaches and integrated treatment strategies, ultimately contributing to better management of patients with combined inflammatory conditions.